Efficient and Stable Red Perovskite Light‐Emitting Diodes via Thermodynamic Crystallization Control - Feng, Shi‐Chi; Shen, Yang; Hu, Xin‐Mei; Su, Zhen‐Huang; Zhang, Kai; Wang, Bing‐Feng; Cao, Long‐Xue; Xie, Feng‐Ming; Li, Hao‐Ze; Gao, Xingyu; Tang, Jian‐Xin; Li, Yan‐Qing (Advanced materials (Weinheim), 2024)
Efficient and stable red perovskite light‐emitting diodes (PeLEDs) demonstrate promising potential in high‐definition displays and biomedical applications. Although significant progress has been made in device performance, meeting commercial demands remains a challenge in the aspects of long‐term stability and high external quantum efficiency (EQE). Here, an in situ crystallization regulation strategy is developed for optimizing red perovskite films through ingenious vapor design. Mixed vapor containing dimethyl sulfoxide and carbon disulfide (CS2) is incorporated to conventional annealing, which contributes to thermodynamics dominated perovskite crystallization for well‐aligned cascade phase arrangement. Additionally, the perovskite surface defect density is minimized by the CS2 molecule adsorption. Consequently, the target perovskite films exhibit smooth exciton energy transfer, reduced defect density, and blocked ion migration pathways. Leveraging these advantages, spectrally stable red PeLEDs are obtained featuring emission at 668, 656, and 648 nm, which yield record peak EQEs of 30.08%, 32.14%, and 29.04%, along with prolonged half‐lifetimes of 47.7, 60.0, and 43.7 h at the initial luminances of 140, 250, and 270 cd m−2, respectively. This work provides a universal strategy for optimizing perovskite crystallization and represents a significant stride toward the commercialization of red PeLEDs. A multifunctional crystallization control strategy by ingenious vapor design is developed for preparing high‐quality perovskite films. The target perovskite films exhibit efficient energy transfer and minimized charge loss. Consequently, a series of red perovskite light‐emitting diodes with record peak external quantum efficiency over 32%, along with remarkable half‐lifetime are obtained.